Health precautions while traveling after COVID-19 - Teitler Regev Sharon; Shosh Shahrabani (Journal of Tourism, Heritage & Services Marketing, 2021)
Purpose: The tourism industry needs to identify potential tourists' planned behavior after COVID-19 and prepare accordingly. This study was conducted in Israel during the initial outbreak of COVID-19. This research focused on different types of precautionary measures used by the tourists and how perceived risk of getting sick with COVID-19 while traveling abroad as well as risk perceptions and attitudes about travel abroad might affect tourists' intentions to adopt precautionary measures when planning future travel abroad. Methods: This research is based on an online survey questionnaire distributed during March 2020 among four hundred and six Israeli participants. Results: The analytical model show that people's with higher levels of attitudes toward traveling abroad and those that prefer to avoid destinations with higher levels of attitudes toward traveling abroad and those that prefer to avoid travel to destinations with various risks had higher intentions to take precautionary measures while traveling abroad. Implications: The results of the current research can assist the tourism industry understand what precautionary measures are important to potential travellers and what health safety assurances the industry must provide to facilitate its recovery in the near future.
Keywords: I15; C38; I1; 330; COVID-19; tourism; health threat perception; future travel avoidance; precautionary measures